Outcomes of primary percutaneous cardiac intervention for ST elevation myocardial infarction with a saphenous vein graft culprit. Issue 1 (23rd December 2019) - Kheifets, Mark; Vaknin‐Assa, Hana; Greenberg, Gabriel; Assali, Abid; Kornowski, Ran; Perl, Leor
Abstract: Background: Patients treated with primary percutaneous coronary intervention (pPCI) for ST elevation myocardial infarction (STEMI) who have a history of coronary artery bypass grafting (CABG) are at high risk of adverse cardiovascular outcomes. Data on the risk of a saphenous vein graft (SVG)—infarct‐related artery (IRA) compared to other culprit vessels are sparse. Methods: The study was based on a prospectively collected registry of 2, 405 consecutive patients with STEMI attending a tertiary medical center in 2001–2017. Patients with an SVG‐IRA ( n = 172) were compared with patients with native vessel disease ( n = 2, 333) for mortality and major adverse cardiac events (MACE), which included death, myocardial infarction (MI), target vessel revascularization (TVR), and coronary artery bypass surgery (CABG) at 1 month and 3 years. Results: The SVG‐IRA group was significantly older than the native vessel group ( p = .05), with no between‐group differences in rates of male patients (76 vs. 82%, p = .59), diabetes (24.2 vs. 26.2%, p = .73), and renal failure (18.8 vs. 9.2%, p = .25). Mortality was higher in the SVG‐IRA group at 1 month (13.9 vs. 2.5%, p < .01) and 3 years (23.9 vs. 7.4%, p < .01). At 3 years, SVG‐IRA was associated with the highest rates of MACE (55.6%), compared with native vessel disease. After correction for confounders, SVG‐IRA remained an independent risk factor for MACE both at 1 month (HR‐2.08, 95%CI 1.72–3.11, p < .01) and 3 years (HR‐2.01, 95%CI 1.28–3.09, p < .01). Conclusion: Among patients treated with pPCI for STEMI, outcomes are worse when the culprit is an SVG.